Les Promesses écrites des composants dans l’architecture de la seconde moitié du XXe siècle - Éric Monin; Catherine Blain (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
During the 1945-1975 period, industrialized products and components allowed to shape a new architecture, made of a wide range of technical and aesthetic innovations. Focusing attention on the finishing work prescribed in the written documents allows to highlight the appearance and power of a vocabulary that revolutionized architectural design and practice. By progressively replacing the neatness of drawings, the precision of the verb introduces an art of prescription based on a variety of new media that are rapidly multiplying. Celebrated in a variety of advertising inserts in professional magazines and within the glossy pages of catalogs and technical brochures distributed by commercial agents in architectural agencies, dozens of new product lines become the material of an architecture transformed by the promises of a brand new glossary. Beyond the visions they arouse, the words and lists they compose, these products reveal the poetry of a world transformed by industry, a material ecstasy that today escapes us, at the risk of forgetting this fragile heritage.